Epigenetic Priming in Childhood Acute Lymphoblastic Leukemia - Raboso-Gallego, Javier; Casado-García, Ana; Isidro-Hernández, Marta; Vicente-Dueñas, Carolina (Frontiers in Cell and Developmental Biology, 2019)
Leukemogenesis is considered to be a process by which a normal cell acquires new but aberrant identity in order to disseminate a malignant clonal population. Under this setting, the phenotype of the leukemic cells is identical to the leukemia-initiating cell in which the genetic insult is taking place. Thus, with some exceptions, B-cell and T-cell childhood leukemias are supposed to arise from B- or T-committed cells. In contrast, several recent studies have revealed that genetic alterations may act in a “hit-and-run” way in the cell-of-origin by imposing the tumor cell identity giving rise to either B-cell or T-cell leukemias. This novel mechanism of cell transformation is mediated by an epigenetic priming mechanism that is established by the initial genetic lesion. This initial hit might be unnecessary for the subsequent tumor evolution and conservation, being the epigenetic priming the engine for the tumor evolution.